Microfluidic droplet application for bacterial surveillance in fresh-cut produce wash waters. - J Brian Harmon; Hannah K Gray; Charles C Young; Kellogg J Schwab (PLoS ONE)
Foodborne contamination and associated illness in the United States is responsible for an estimated 48 million cases per year. Increased food demand, global commerce of perishable foods, and the growing threat of antibiotic resistance are driving factors elevating concern for food safety. Foodborne illness is often associated with fresh-cut, ready-to-eat produce commodities due to the perishable nature of the product and relatively minimal processing from farm to the consumer. The research presented here optimizes and evaluates the utility of microfluidic droplets, also termed ultra-miniaturized bioreactors, for rapid detection of viable Salmonella enterica ser. Typhimurium in a shredded lettuce wash water acquired from a major Mid-Atlantic produce processing facility (denoted as Producer) in the U.S. Using a fluorescently-labeled anti-S. Typhimurium antibody and relative fluorescence intensities, paired with in-droplet incubation, S. Typhimurium was detected and identified with 100% specificity in less than 5 h. In initial optimization experiments using S. Typhimurium-spiked sterile water, the relative fluorescence intensity of S. Typhimurium was approximately two times that of the observed relative intensities of five non-S. Typhimurium negative controls at 4-h incubation in droplets containing Rappaport-Vasiliadis (RV) broth at 37°C: relative fluorescence intensity for S. Typhimurium = 2.36 (95% CI: 2.15-2.58), Enterobacter aerogens 1.12 (95% CI: 1.09-1.16), Escherichia coli 700609 = 1.13 (95% CI: 1.09-1.17), E. coli 13706 1.13 (95% CI: 1.07-1.19), E. coli 700891 1.05 (95% CI: 1.03-1.07) and Citrobacter freundii 1.04 (95% CI: 1.03-1.05). S. Typhimurium- and E. aerogens-spiked shredded lettuce wash waters acquired from the Producer were then incubated 4 h in-droplet at 37°C with RV broth. The observed relative fluorescence of S. Typhimurium was significantly higher than that of E. aerogens, 1.56 (95% CI: 1.42-1.71) and 1.10 (95% CI: 1.08-1.12), respectively. While further optimization focusing on compatible concentration methodologies for highly-dilute produce water samples is needed, this application of droplet microfluidics shows great promise in dramatically shortening the time necessary-from days to hours-to confirm viable bacterial contamination in ready-to-eat produce wash waters used throughout the domestic and international food industry.